Análise da ocorrência de condomínios horizontais: o caso de Santa Maria, RS - Silva, Mariana Almeida da (2023)
The growing Brazilian urbanization is stamped by social and environmental impacts, but it is also necessary to observe spatial inequality. Characterized by housing phenomena and real estate speculation, the occurrence of horizontal condominiums is a consequence of spatial inequality. However, it is observed that this phenomenon causes impacts on urban landscape, which raises questions about its application and sustainable urban development. The object of study was the city of Santa Maria, RS, which presents an intense flow of new condominium developments in its territory. This work aimed to understand how the process of occurrence of horizontal condominiums in the city occurred, and what its configuration and current implications. A geographical, historical and legislative survey was carried out, based on data from the IBGE and from the archives of the Municipality of Santa Maria, generating registration forms, and also the spatialization of the information found in thematic maps. The survey of horizontal condominiums showed that the developments are concentrated in specific areas of the city, and that their occurrence began to spread in character from 2010. It is observed that the analyzed city has a high occurrence of condominiums, which in the vast majority in peripheral areas of neighborhoods with a high level of 'social commitment', which contributes to social inequality.